Learning Platforms Both of Conventional and Online Educational Systems: Perspectives on Blended Learning - Titis Widiyani; Hari Widi Utomo (Educalitra: English Education, Linguistics, and Literature Journal, 2024)
The purpose of this study was to find out how using the platform from the perspective of both teachers and students can help to enhance the teaching and learning process at the University of Muhammadiyah Purwokerto for Master's Degree Students. The Pandemic gave a lot of benefits in the educational field. As we know online learning has been used since a long time ago supporting teaching and learning material using the website. Many people create an application and modern websites like Zoom, G-meet, on class, etc. That application supported almost everyone because it allowed for the flexible delivery of information via audio-visuals no matter time or place. However, online learning also needs to be implemented to know students’ motivation, responsibility, and learning behavior. Problem-solving that the University of Muhammadiyah Purwokerto used was implementing blended learning both online 60% and offline 40%. The data collection was an open-ended questionnaire that delivered questions to one lecturer, one international student, and 7 national students through G-Form. Inductive analysis was utilized using the data. As a result, all of the respondents gave positive and agreement perspectives on blended learning because it could make students learn autonomously, manage time more flexibly, enhance student achievement, and be confident when offline class.